2014
DOI: 10.1007/s00438-014-0969-3
|View full text |Cite
|
Sign up to set email alerts
|

Diversification and distinctive structural features of S-RNase alleles in the genus Solanum

Abstract: The multigenic and multiallelic S-locus in plants is responsible for the gametophytic self-incompatibility system, which is important to prevent the detrimental effects of self-fertilization and inbreeding depression. Several studies have discussed the importance of punctual mutations, recombination, and natural selection in the generation of allelic diversity in the S-locus. However, there has been no wide-ranging study correlating the molecular evolution and structural aspects of the corresponding proteins i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 70 publications
1
7
0
Order By: Relevance
“…Amino acid sequence variation within S-RNase was observed among S. tub _S p5 , S. tub _S t5 , and S. tub _S t6 alleles (Figure 1A). Nearly half of these variants were within the hypervariable domains (HVa and HVb) and not in conserved domains (C1-5) consistent with data that show the S-RNase variable regions are the determinants for allele specificity in different Solanum species (Matton et al, 1997, 1999; Brisolara-Corrêa et al, 2015). Specifically, four amino acids within these variable regions (T74, N76, Y77, and R101) have been reported as the sole factors for allele conversion of the pollen rejection phenotype in S. chacoense (Matton et al, 1997).…”
Section: Discussionsupporting
confidence: 87%
“…Amino acid sequence variation within S-RNase was observed among S. tub _S p5 , S. tub _S t5 , and S. tub _S t6 alleles (Figure 1A). Nearly half of these variants were within the hypervariable domains (HVa and HVb) and not in conserved domains (C1-5) consistent with data that show the S-RNase variable regions are the determinants for allele specificity in different Solanum species (Matton et al, 1997, 1999; Brisolara-Corrêa et al, 2015). Specifically, four amino acids within these variable regions (T74, N76, Y77, and R101) have been reported as the sole factors for allele conversion of the pollen rejection phenotype in S. chacoense (Matton et al, 1997).…”
Section: Discussionsupporting
confidence: 87%
“…Recently, a ‘collaborative non‐self recognition’ system of S‐RNase‐based SI in Solanaceae was proposed, in which the product of each SLF interacts with a subset of non‐self S‐RNases, and the products of multiple SLF types are required for the entire collection of non‐self S‐RNases to be collectively recognized (Kubo et al ., ). Recent studies have shown two hypervariable regions of S‐RNases, named HVa and HVb, are involved in their specificity and both regions are exposed on the protein surface (Matton et al ., , ; Ida et al ., ; Matsuura et al ., ), and most positively selected sites are located in the HV regions of S‐RNase of the Solanaceae, supporting an important role of the HV regions in their specific recognition (Vieira et al ., ; Brisolara‐Correa et al ., ). SLF is an F‐box protein with a conserved F‐box domain at the N terminus.…”
Section: Introductionmentioning
confidence: 97%
“…Domain-swapping transgenic experiments with similar S-RNase alleles have showed that the two hypervariable regions of S-RNases , are involved in specificity determination (Ide et al, 1991; Matton et al, 1997, 1999; Matsuura et al, 2001). Although there are positively selected amino acid sites in these regions, there are other amino acid sites in other regions of the S -pistil gene, that may be involved in recognition of the S -pollen gene(s) (Vieira et al, 2007; Brisolara-Correa et al, 2015). To address S -pollen specificity, Petunia SLF1 gene has been divided into three functional domains (FD1 from amino acid position 1 to 110; FD2, from amino acid position 110 to 260, and FD3 from amino acid position 260 to 389), and in vivo assays performed.…”
Section: Introductionmentioning
confidence: 99%